Long‐term sevoflurane exposure reduces the differentiation potential and hypoxia tolerance potential of neural stem cells. Issue 8 (3rd November 2021) - Gao, Wenbo; Bai, Yunxiao; Ma, Xiaofang; Bian, Xiyun; Xu, Jingman; Xue, Na; Yu, Tian; Liu, Xiaozhi; Bai, Yaowu; Chu, Dongmei
Abstract: Purpose: To investigate the effect of prolonged sevoflurane (SEV) exposure on differentiation potential and hypoxia tolerance of neural stem cells (NSCs). Materials and methods: NSCs were extracted from 15‐day fetal mice. After sub‐culture, SEV exposure treatment was performed. Cell cycle were detected by flow cytometry. Western blot and immunofluorescence assay were used to detect the expression and spatial distribution of Nestin, NSE, GFAP, Oct4, and SOX2; CCK‐8 detected cell viability. Cell growth morphology was observed under a microscope. TUNEL detected cell apoptosis; the concentration of extracel‐lular lactate dehydrogenase (LDH) was determined by ELISA. Results: Compared with the control group, the proportion of NSCs in the G2/M phase increased in the SEV exposure group; our results also suggested the sphere‐formation rate decreased significantly, increased apoptosis and decreased cell viability. Besides, the level of LDH release increased. Conclusion: Long‐term exposure to SEV (>8 h) promoted the premature differentiation of NSCs and reduced their pluripotency, reserves, and hypoxia tolerance. This study reveals the reasons underlying damage to the nervous system of young children induced by long‐term exposure to SEV from the perspective of CNS reserve cells. Abstract : In this study, we used mouse neural stem cells (NSCs) cultured in vitro as the research object. Our findings show that long‐term sevoflurane anesthesia (>8 h) reduced the proliferation potential, promoted differentiation, increased cell apoptosis, and reduced the hypoxia tolerance of NSCs.